Temporal and Spatial Variability of Limnological Characteristics in Areas under the Influence of Tilapia Cages in the Chavantes Reservoir, Paranapanema River, Brazil - Monteiro Rezende Ayroza, Daercy Maria; Nogueira, Marcos Gomes [UNESP]; Da Silva Ayroza, Luiz Marques; Carvalho, Edmir Daniel [UNESP]; Ferraudo, Antonio Sergio [UNESP]; Monteiro Camargo, Antonio Fernando [UNESP] (Wiley-Blackwell, 2013)
The influence of tilapia cages on limnological characteristics of the Chavantes Reservoir, Paranapanema River, Brazil, was investigated in March and June 2007. Principal components analysis was used to compare the transparency; dissolved oxygen; temperature; total organic nitrogen, phosphorus, and dissolved solids; chlorophyll aand electrical conductivity of fish farm 1 (239.3m.t.), 2 (461.5m.t.) and areas without cages, in the lacustrine and river-reservoir transition regions. The variables differentiated the regions and areas with and without cages. In March, in the lacustrine region, there was a thermal and chemical stratification, and in the transition region, there was a temperature and oxygen reduction gradient between the surface and bottom that was also observed in June in fish farm 1. The higher transparency confirmed the increased light penetration in the lacustrine region. In the transition region, there were higher turbidity, total dissolved solid, and conductivity values that are likely related to allochthonous material flow and transport. In fish farms, lower oxygen and pH values indicate intense decomposition and respiration. The generally higher total dissolved solid and nutrient values, turbidity, and conductivity and the lower transparency in one or both fish farms indicate their contribution to eutrophication, demonstrating the need for careful monitoring.